2017
DOI: 10.1111/tbed.12706
|View full text |Cite
|
Sign up to set email alerts
|

Simplifying sampling for African swine fever surveillance: Assessment of antibody and pathogen detection from blood swabs

Abstract: SummaryAfrican swine fever (ASF) is a notifiable disease with serious socio-economic consequences that has been present in wild boar in the Baltic States and Poland since2014. An introduction of ASF is usually accompanied by increased mortality, making fallen wild boar and hunted animals with signs of disease the main target for early warning and passive surveillance. It is difficult, however, to encourage hunters and foresters to report and take samples from these cases. A pragmatic and easy sampling approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 23 publications
0
32
0
2
Order By: Relevance
“…Along these lines, several approaches have been assessed in the recent past. Specifically, the applicability of different dry blood swabs [ 11 , 12 ], dried filter papers and FTA cards [ 13 , 14 , 15 ], fecal samples [ 16 ], oral, nasal and rectal swabs [ 17 ], meat-juice [ 18 ], and different rope-based options [ 19 , 20 ] has been assessed. Further matrices such as intraocular fluid, superficial lymph nodes (e.g., inguinal lymph nodes), ear punches following the example of BVDV diagnosis [ 21 ], and the like have been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Along these lines, several approaches have been assessed in the recent past. Specifically, the applicability of different dry blood swabs [ 11 , 12 ], dried filter papers and FTA cards [ 13 , 14 , 15 ], fecal samples [ 16 ], oral, nasal and rectal swabs [ 17 ], meat-juice [ 18 ], and different rope-based options [ 19 , 20 ] has been assessed. Further matrices such as intraocular fluid, superficial lymph nodes (e.g., inguinal lymph nodes), ear punches following the example of BVDV diagnosis [ 21 ], and the like have been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study investigating the detection of African swine fever virus DNA in serum or dry blood swabs of experimentally infected pigs found no diference in the detection rates between these two sample types ater storage for 8 days at room temperature. 17 Diferences between studies may be due to the diferent viral load in the original samples, virus structure (RNA vs DNA) and swab type used. In this study, the lowest PRRSV RNA detection was in FTA cards (48.9 per cent).…”
Section: Discussionmentioning
confidence: 99%
“…Passive surveillance of deceased wild boar and symptomatic animals could serve as first indicators of ASFV activity in new area of introduction (97,98). Petrov et al demonstrated that molecular detection of ASFV as well as classical swine fever virus were also detected reliably by quantitative PCR from dry and semi-dry blood swabs collected from carcasses (98).…”
Section: Surveillancementioning
confidence: 99%
“…Petrov et al demonstrated that molecular detection of ASFV as well as classical swine fever virus were also detected reliably by quantitative PCR from dry and semi-dry blood swabs collected from carcasses (98). Similarly, Carlson et al evaluated the reliability of detecting ASFV antibody from blood swabs taken from deceased animals in the field using commercially-available antibody-based detection kits (97). Sensitivity and specificity of these kits on dried blood swabs wellexceeded 90%.…”
Section: Surveillancementioning
confidence: 99%